Impact of long-term quorum sensing inhibition on uropathogenic Escherichia coli. (6th January 2021) - Henly, E L; Norris, K; Rawson, K; Zoulias, N; Jaques, L; Chirila, P G; Parkin, K L; Kadirvel, M; Whiteoak, C; Lacey, M M; Smith, T J; Forbes, S
Abstract: Background: Quorum sensing is an extracellular bacterial communication system used in the density-dependent regulation of gene expression and development of biofilms. Biofilm formation has been implicated in the establishment of catheter-associated urinary tract infections and therefore quorum sensing inhibitors (QSIs) have been suggested as anti-biofilm catheter coating agents. The long-term effects of QSIs in uropathogens is, however, not clearly understood. Objectives: We evaluated the effects of repeated exposure to the QSIs cinnamaldehyde, (Z)-4-bromo-5(bromomethylene)-2(5H)-furanone-C30 (furanone-C30) and 4-fluoro-5-hydroxypentane-2, 3-dione (F-DPD) on antimicrobial susceptibility, biofilm formation and relative pathogenicity in eight uropathogenic Escherichia coli (UPEC) isolates. Methods: MICs, MBCs and minimum biofilm eradication concentrations and antibiotic susceptibility were determined. Biofilm formation was quantified using crystal violet. Relative pathogenicity was assessed in a Galleria mellonella model. To correlate changes in phenotype to gene expression, transcriptomic profiles were created through RNA sequencing and variant analysis of genomes was performed in strain EC958. Results: Cinnamaldehyde and furanone-C30 led to increases in susceptibility in planktonic and biofilm-associated UPEC. Relative pathogenicity increased after cinnamaldehyde exposure (4/8 isolates), decreased after furanone-C30 exposure (6/8 isolates) and varied after F-DPD exposure (one increased and one decreased). A total of 9/96 cases of putative antibiotic cross-resistance were generated. Exposure to cinnamaldehyde or F-DPD reduced expression of genes associated with locomotion, whilst cinnamaldehyde caused an increase in genes encoding fimbrial and afimbrial-like adhesins. Furanone-C30 caused a reduction in genes involved in cellular biosynthetic processes, likely though impaired ribonucleoprotein assembly. Conclusions: The multiple phenotypic adaptations induced during QSI exposure in UPEC should be considered when selecting an anti-infective catheter coating agent.